The construction of the Amazon Peruvianness: the case of the Fourth Centenary of the Discovery of the Amazon River in 1942 - Herrera, Morgana (2018)
In 1941, Peruvian president Manuel Prado declared by official decree that the year 1942 be dedicated to the celebration of the Fourth Centenary of the Discovery of the Amazon River which he described as the “crowning achievement of our nationality integration”. In the aftermath of the Ecuadorian- Peruvian war of 1941 and in the context of the renewal of the rubber extraction, the fourth centenary proved to be unprecedented in the production of speeches on Peruvian identity and the Amazon. This work shows how an attempt was made to incorporate the Amazonia into the national identity by reviving and updating clichés about the jungle.